Detection of germline mutations in the von Hippel-Lindau disease gene by the primer specified restriction map modification method. Issue 12 (December 1995) - Kishida, T; Chen, F; Lerman, M I; Zbar, B
Abstract : Von Hippel-Lindau disease (VHL) is an inherited disorder characterised by a predisposition to develop tumours in the eyes, central nervous system, kidneys, and adrenal glands. Recently the VHL gene was cloned and shown to be mutated in 75% of US and Canadian VHL families. To develop simple, rapid methods for the detection of mutations found in large numbers of affected people, we designed based on the primer specified restriction site modification method. These tests have proved useful in identifying asymptomatic mutated VHL gene carriers who have the nt 505 T to C mutation or the nt 686 T to C mutation. Together with an MspI digestion test which can detect a mutation hot spot in codon 238, polymerase chain reaction/restriction endonuclease based tests can now detect VHL mutations in more than 50% of VHL type 2 families.